The implementation of a caring safety model to decrease adverse events - Menap, Menap; Putra, Made Mahaguna (International Journal of Public Health Science (IJPHS), 2024)
Patient safety is the most crucial health service orientation. An appropriate clinical risk management system is needed to sustain the safety culture in the hospital. This study aimed to examine the implementation of the caring safety model (CSM) in reducing the adverse events (AEs) in patients. A quasi-experimental design (pretest-posttest control group design) was conducted, involving samples in two hospitals in Indonesia. Nurses in the experimental group followed the CSM training and applied it to nursing care, while nurses in the control group followed the standard care. AEs were assessed on indicators of medication error, patient falls, phlebitis, decubitus, and surgical site infection. The implementation of CSM was evaluated for it is impact on AEs reduction. CSM-based care could reduce AEs in patients better than standard care. The final observation variable of the experimental and the control groups resulted in a value of sig of